Three‐Dimensional Accuracy of Guided Implant Placement: Indirect Assessment of Clinical Outcomes. (15th December 2011) - Platzer, Susanne; Bertha, Georg; Heschl, Alexander; Wegscheider, Walther A.; Lorenzoni, Martin
ABSTRACT Purpose: Precise preoperative implant planning and its exact intraoperative transfer are crucial for successful implant‐supported rehabilitation of partially or completely edentulous patients. In the present pilot study, optical laser scanning was used to evaluate deviations between three‐dimensonal computer‐assisted planned and actual implant positions by indirect methods. Material and Methods: Five patients receiving a total of 15 implants were included in this study. The used planning software was SimPlant 12.0 (Materialise Dental, Leuven, Belgium) to visualize the implant positions, and with an appropriate guided surgery protocol (Navigator™, Biomet 3i, Palm Beach Gardens, FL, USA) implant positions were implemented via tooth‐supported stereolithografic surgical guides. All implants (Osseotite™, Biomet 3i) were inserted in a flapless approach and immediately provided with prefabricated temporary splinted restorations. Intraoral pickup impressions were taken postoperatively, and the implant positions of the master casts were compared with presurgical casts. Implant replica deviations were evaluated by three‐dimensional optical laser scanning providing distances and angulations between implant replicas. Results: Overall, the postsurgical implant replica positions were found to deviate from the positions in the preoperative cast by a mean of 0.46 ± 0.21 mm (range: 0.09–0.85 mm). Positional deviations were 0.27 ± 0.19 mm (range: 0.04–0.60 mm) along the x‐axis representing the buccal‐lingual directions, 0.15 ± 0.13 mm (range: 0.0–0.34 mm) along the y‐axis representing the ventrodorsal direction, and 0.28 ± 0.19 mm (range: 0.02–0.59 mm) along the z‐axis representing cranial and apical directions. Rotational deviations amounted to 14.04 ± 11.6° (range: 0.09–36.47°). Conclusions: The results of this pilot study demonstrate precise transfer of implant replica position by means of simulated guided implant insertion into a preoperative cast and a postoperative cast obtained from impressioning. Further studies are needed to identify appropriate evaluation techniques and mechanisms to increase the transfer precision of three‐dimensional planning and guiding systems.